Agilizing the enterprise : collaborative leadership, dynamic strategy, and orginizational flexibility - Raynus, Joseph (CRC Press, Taylor & Francis Group, 2018)
re you still searching for the workplace that deserves someone like you? Do you really have a good understanding about what is going on out there, in the business world? In this book, we will discuss the importance of agility and how it affects the solutions that are being delivered by an organization. We will also talk about how a blend of strategic innovation, visionary leadership, and organizational agility go hand in hand to ensure the success of an organization. Enterprise agility is not a far-fetched possibility. Once the problems of the organization are identified, with the right tools and effort, the agility, efficiency, and effectiveness of an organization, as well as the processes that the success of the organization are based on, can all be maximized. This book will broaden your thinking and will help you expand your horizons" -- From the publisher.